Rekayasa Sosial pada Usaha Tani Beresponsif Gender di Kawasan Program Food Estate, Provinsi Kalimantan Tengah - Ikhwan, Rizghina; Syahyuti; Suharyono, Sri (Analisis Kebijakan Pertanian, 2025)
Women contribute significantly to every farming activity. However, there are still agricultural development programs that do not respond to women’s involvement. One of the government’s current priority programs is Food Estate in Kapuas and Pulang Pisau Regencies, Central Kalimantan Province. This study aims to understand and propose recommendations for developing social engineering in gender-responsive farming in the Food Estate in Central Kalimantan. Data and information were collected from the location of the Food Estate and supported by various literature on social engineering in gender-responsive farming. The study results show that farming in Bataguh District, Kapuas Regency, and Padih Batu District, Pulang Pisau Regency, indicates the potential for gender inequality. From the results of this study, it is suggested that the development of the Food Estate program be carried out with social engineering in an efficient, effective planning and policy to achieve justice and gender equality. Social engineering aims to realize gender equity in farming which can increase the productivity and competitiveness of farming businesses. On an ongoing basis, it is necessary to identify the needs of male and female farmers in each farming activity to create gender sensitivity.